To solve the problem, we first need to establish the equation for direct variation. If \( y \) varies directly with \( x \), we can express this relationship as:
\[ y = kx \]
where \( k \) is the constant of variation.
Given \( y = 5 \) when \( x = 55 \), we can find \( k \):
\[ 5 = k \cdot 55 \]
To isolate \( k \), we divide both sides by 55:
\[ k = \frac{5}{55} = \frac{1}{11} \]
Now that we have \( k \), we can write the direct variation equation:
\[ y = \frac{1}{11}x \]
Next, we need to find the value of \( y \) when \( x = 22 \):
\[ y = \frac{1}{11} \cdot 22 \]
Calculating this gives:
\[ y = \frac{22}{11} = 2 \]
Thus, when \( x = 22 \), \( y = 2 \).
The correct response is:
When x=22, y=2.
or
When x equals 22, y equals 2.